ChemInform Abstract: Organo‐Manganese η2‐Auxiliary Directed Reactions: A Diastereoselective Approach to 2, 3‐Allenols. Issue 27 (18th June 2015) - Roy, Animesh; Bhat, Bilal A.; Lepore, Salvatore D.
Abstract The recently published complexation of chiral allenyl aldehydes with methylcyclopentadienyl manganese tricarbonyl efficiently addresses the weak stereoinduction of the allenic moiety by transmitting the chiral information closer to the aldehyde group.